2021
DOI: 10.1101/2021.07.14.451852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Analyses of Postnatal Liver Development and Maturation by Single Cell Transcriptomics

Abstract: Liver is the major metabolic organ, although its postnatal development and maturation are inadequately understood. We analyzed 52,834 single cell transcriptomes and identified 31 cell types or states in mouse livers at postnatal day 1, 3, 7, 21 and 56. We observed unexpectedly high levels of hepatocyte heterogeneity in the developing liver and progressive construction of the zonated metabolic functions from pericentral to periportal hepatocytes, which was orchestrated with development of sinusoid endothelial, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…We further validated these differences between normal neonatal and adult HSCs using the scRNA‐seq data generated by a recent study on mouse liver postnatal development (Figure ). [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…We further validated these differences between normal neonatal and adult HSCs using the scRNA‐seq data generated by a recent study on mouse liver postnatal development (Figure ). [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…Cd74 + /Clec9a + /H2- Aa + /Irf8 + /Siglech + /Runx2 + /CD7 + Dendritic cells (DCs), F13a1 + /S100a6 + /Ly6c2 + Macrophages, Mpo + /Elane + /Prtn3 + /Fcnb + /Ngp + /Chil3 + Neutrophil progenitors I and II, Cd177 + /Stfa2 +/ Mmp8 + /Asprv1 + Neutrophils, Mcpt8 + /Gata2 + /Cpa3 + Mast cells; ii) the Lymphoid lineage Ltb + /Igll1 + /Il7r + /Cd19 + /Ebf1 + /Igkc +/ Cd79a/b + B-cells; and iii) Erythroid cells including Car1 + /Gata1 + /Klf1 + progenitors, Mt2 + /Tfrc + /Slc4a1 + /Hemgn + Erythroblasts, Gypa + /Bpgm + /Hba-a2 + Erythrocytes, and Itga2b + (Cd41 + )/Treml1 + /Pf4 + Megakaryocytes. The scRNA seq also revealed the presence of population of Ncr1 + /Gzma + /Tbx21 + NK(T) cells, coming from both fetal thymus and liver [4,[75][76][77][78] (Fig. 2B, C).…”
Section: Comprehensive Single Cell Analysis Identifies a Reduction In...mentioning
confidence: 86%
“…How the pediatric liver responds to cholestasis during the pediatric hematopoietic to metabolic shift [2,4] is poorly understood. In the adult cholestatic liver, bile acids activate hepatocytes, which then secrete cytokines to attract lymphocytes [81].…”
Section: Delayed Hepatocyte Maturation and Diminished Hepatocyte Acti...mentioning
confidence: 99%
“…Different from whole-tissue RNA sequencing analysis, scRNA-seq, spatial transcriptomics, and emerging single-cell multimodal omics endowed the study of transcriptional activity at the single-cell or spatial level, further broadening our understanding of tissue-cell interaction in situ-for example, under physiological conditions, scRNA-seq analyzed the livers of mice at 1, 3, 7, 21, and 56 days after birth and identified myeloid cell subsets at different time points, including a unique source of Dcn + Mac from day 7 (11). At these periods, there was a stable Wnt signal in the interaction between KCs and hepatocytes, but a unique NOV-NOTCH1 signal interaction was produced in D7.…”
Section: Vistamentioning
confidence: 99%
“…Extensive mouse and human research have shown that neutrophils and macrophages exert a pivotal part in the foundation, development, and reversion of liver diseases, including in guiding tissue remodeling. With the progress of technology, more and more myeloid cell subtypes have been identified and located by single-cell multimodal omics (8)(9)(10)(11)(12). Each myeloid type acts as a unique individual participating in the immune response.…”
Section: Introductionmentioning
confidence: 99%